ANALYSIS OF THE LEVEL TAXPAYER COMPLIANCE AFTER THE REDUCTION IN THE SME TAX RATE - Siska Aulia Rahma (Journal of Taxation Analysis and Review, 2021)
Taxes are the largest source of state revenue, so the government seeks to increase tax revenues by implementing policies that can later attract people to pay taxes. The purpose of this study was to analyze the level of taxpayer compliance after the decrease in the tax rate of SME in Subang Regency. This type of research is quantitative research. The population in this study is SME located in Subang Regency. The research sampling method used purposive sampling, namely the determination of the sample randomly by taking respondents totaling 40 SME actors. Data was collected by distributing questionnaires to SME actors. The analysis technique uses simple linear regression analysis. The results showed that the coefficient value of the determinant R2 was 0.591, which means that the dependent variable can be explained by the independent variable of 59.1% and the remaining 40.9% is explained by other variables. The results of this study conclude that the level of taxpayer compliance has an effect after the decrease in the SME tax rate.